Impacto de la emergencia sanitaria dentro del rendimiento del talento humano en las empresas públicas y privadas en el área administrativa. - Guerra, Marino R. (2021)
At the end of 2019, the global pandemic caused by SARS-COV2 begins, then called covid19 which at the beginning of 2020 reaches Ecuador, before this the health emergency is declared throughout the country affecting the sectors, causing fear of ignorance of thedisease which causes many deaths, as a result of this the companies had to paralyze theiractivities and change work habits, this is why it is intended to design tools to obtaininformation on the conditions of public and private workers, therefore It is proposed to carryout the study of the impact of the health emergency within the performance of human talentin public and private companies, so it is proposed to carry out a research with a qualitativeapproach, of a descriptive and explanatory research level, with a type documentary research,to propose collection techniques as evaluation mechanisms, the survey and the focus groupal, for which these instruments for the collection and processing of information weredesigned, therefore, being an innovative research topic, it will serve as a precedent for futureresearch topics, while it will help consultants or companies through the human resourcesdepartments. who decide to apply the tools designed by means of evaluation instruments thatwill be used to measure the impact of the health emergency since until the present date ofcompletion of the projects the employees are forced to carry out their daily activities with the insecurity of the pandemic.